Two polyoxometalate-based metal–organic complexes constructed from a pyridine-polyazole: Assembly, structures, electrochemistry and adsorption properties. (1st July 2019) - Bai, Xue; Lin, Hongyan; Wang, Xiuli; Sun, Junjun; Wang, Xiang; Liu, Guocheng
Graphical abstract: Two new polyoxometalate-based metal–organic complexes with rigid pyridyl-triazole-tetrazole ligand and two different polyoxometalates have been prepared and characterized. The electrochemical behaviors and the adsorption activities have been described. Abstract: Two new polyoxometalate-based metal–organic complexes, namely, [Ni3 (Htyptz)2 (γ-Mo8 O26 )(H2 O)8 ]·4H2 O (1 ) and [Ni3 (H2 typtz)2 (TeMo6 O24 )(H2 O)8 ]·6H2 O (2 ) [H2 typtz = 3-(tetrazol-5-yl)-5-(pyrid-3-yl)-1, 2, 4-triazole] have been successfully synthesized under hydrothermal conditions. Their structures have been identified by single crystal X-ray diffraction, and further characterized by elemental analysis, infrared spectra (IR), and powder X-ray diffraction (PXRD). In complex1, the [Ni(Htyptz)2 ] mononuclear unit link the adjacent 1D Ni-γ-Mo8 O26 inorganic chains conducing to the formation of the 2D layer, then the adjacent 2D layers are connected through hydrogen bonds to construct a 3D supramolecular network. Complex2 is a 2D coordination network, which is constructed from 1D [Ni3 (H2 typtz)2 ] chains and TeMo6 anions. The different polyoxometalates play important roles in tuning the structures of the title complexes. In addition, the adsorption activities of complexes1 and2 for methylene blue (MB), neutral red (NR), rhodamine 6G (R6G), Orange II (OrII) have been investigated. Moreover, their electrochemical behaviors and electrocatalytic properties have also been studied.